2014
DOI: 10.1111/jpn.12192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oleuropein supplementation on growth performance, serum lipid concentrations and lipid oxidation of Japanese quails

Abstract: An in vivo experiment was conducted to compare the effects of dietary supplementation with oleuropein and/or α-tocopheryl acetate on growth performance, serum lipid concentrations and lipid oxidation of Japanese quail meat during refrigerated storage. Performance and slaughtering parameters were not affected by dietary treatments. The diets supplemented with oleuropein at the levels of 150 or 200 mg/kg were more effective in delaying lipid oxidation in breast and thigh meats compared with the control diet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
7
21
0
Order By: Relevance
“…The results with respect to blood parameters are in agreement with the results of previous studies (Coni et al, 2000;Andreadou et al, 2006;Sarica and Toptas, 2014). Indeed, it has been reported that the addition of oleuropein to the diet reduced the plasmatic levels of total (Coni et al, 2000;Andreadou et al, 2006), free, and ester cholesterols (Andreadou et al, 2006), as well as triglycerides (Coni et al, 2000;Andreadou et al, 2006) in rabbits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results with respect to blood parameters are in agreement with the results of previous studies (Coni et al, 2000;Andreadou et al, 2006;Sarica and Toptas, 2014). Indeed, it has been reported that the addition of oleuropein to the diet reduced the plasmatic levels of total (Coni et al, 2000;Andreadou et al, 2006), free, and ester cholesterols (Andreadou et al, 2006), as well as triglycerides (Coni et al, 2000;Andreadou et al, 2006) in rabbits.…”
Section: Discussionsupporting
confidence: 92%
“…In some studies, dietary oleuropein supplementation improved the performance of broilers (El-Damrawy et al, 2013;Jabri et al, 2017), laying hens (Cayan and Erener, 2015;Ahmed et al, 2017), and quail (Bahsi et al, 2016). In contrast to these reports, oleuropein supplementation at increasing levels exerted no growth-promoting effect when incorporated into quail diets (Sarica and Toptas, 2014).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…On the other hand, in the past years, the leaves of Olea europaea L. have been considered as an important source of antioxidant compounds. In this case, OL is the most predominant and active phenolic compound (60-90 mg/g dried olive leaves), and it is usually considered as an antioxidant reference in comparison with other secoirioids [45,46]. OL contains active components in its molecule with conferred a potential antioxidant activity.…”
Section: Functional and Physiological Chemistry Of The Main Secoiridomentioning
confidence: 99%
“…Moreover, Özdemir and Azman (25) conducted a study to determine the effects of addition of olive leaf extract to quail mixed feeds on yield performance and found that the lowest saturated fatty acid ratios in egg yolk were determined in oleuropein added group. In the another study Sarıca and Toptaş (27) reported that supplemented with oleuropein at the levels of 150 or 200 mg/kg had significantly the highest polyunsaturated fatty acid and omega-3 fatty acid contents in thigh meat, and levels of the oleuropein supplementation didn't affect performence parameters in quails.…”
Section: Discussionmentioning
confidence: 99%